PROTEIN AND BETA AMYLASE EXTRACTION TO INCREASE SWEET POTATOâS ADDED VALUE - Chendikia, Zisma
Sweet potato is a high producing food because its ability to survive and adapt to wide range of conditions. Also, sweet potato contains high protein which most of it is ?-amylase. ?-amylase itself is an exoenzymatic enzyme which acts specifically to cut 1,4 glycosidic bond on starch so that it will give sweet taste to starch. That is why, ?-amylase can be used as the material of maltose syrup production, which is widely used on foods, such as ice cream and candy. The removal of ?-amylase from sweet potato is very advantageous in process of making sweet potato flour because it can remove the sweet taste that dominates sweet potato flour. The goals of this research are to extract and to decide the influence of extraction condition of ?-amylase from sweet local sweet potato, also to test ?-amylase application of making maltose syrup. Variations that will be used are variety of sweet potato which are cilembu and white sweet potato, extraction pH which will be varied on pH 2, 3, 5, 7, 9, 11, and the use of reducing agent in extraction process, that is sodium metabisulfit. This research will be done by extracting the protein from sweet potato using water as the solvent. To separate crude extract and its residue, orbital shaker and centrifuge are used. After that, crude extract is precipited on its isoelectric point to separate protein furthermore. The protein on the sediment the liquid then tested to check the amount of protein and the activity of the enzyme. From this research, it can be concluded that reducing agent (natrium metabisulfite) with concentration 1,5 g/L could affect the amount of protein extraction and the activity of beta amylase enzyme. White sweet potato have greater amount of protein and beta amylase activity than cilembu sweet potato. The highest activity of enzyme is at crude extract extracted at pH 5. The highest emount of protein is at crude extract extracted at pH 9 and the isoelectric point of sweet potato protein is at pH 3.